Residential radon, genetic polymorphisms in DNA damage and repair-related. (September 2019) - Lorenzo-González, María; Ruano-Ravina, Alberto; Torres-Durán, María; Kelsey, Karl T.; Provencio, Mariano; Parente-Lamelas, Isaura; Leiro-Fernández, Virginia; Vidal-García, Iria; Castro-Añón, Olalla; Martínez, Cristina; Golpe-Gómez, Antonio; Torres-Español, María; et al.
Highlights: The incidence of lung cancer in never-smokers is increasing. Residential radon exposure is the first cause of lung cancer in never-smokers. Certain polymorphisms also contribute to lung cancer individual susceptibility. There is an effect modification between some polymorphisms and residential radon. Abstract: Objectives: To analyze the relationship of GSTT1, GSTM1, XRCC1 (rs25487), ERCC1 (rs11615, rs3212986), ERCC2 (rs13181), XRCC3 (rs861539), OGG1 (rs1052133), and Alpha-1-Antitrypsin mutations (AAT) with the risk of lung cancer in never-smokers, and ascertain if there is an effect modification between these polymorphisms and residential radon exposure. Material and methods: We designed a multicenter hospital-based case-control study in a radon-prone area. 322 cases and 338 controls, all never-smokers, were included. They were selected using a frequency sampling based on sex and age distribution of the cases. Participants donated 3 ml. of whole blood used to determine genotype for polymorphisms. They placed a radon detector to measure residential radon exposure in their dwelling. Results: The OR for deleted GSTM1 patients was 3.46 (95% CI = 1.52–7.89) at residential radon exposures above 200 Bq/m 3 . The ERCC1 rs3212986 polymorphism was the most associated with the risk of developing lung cancer, both for low and high radon exposures. The ERCC1 rs321986 GT and TT genotypes (at radon concentrations >200 Bq/m 3 ) were more significantly associated with higher lung cancer risk (OR = 2.40, 95% CI = 1.29–4.45; OR = 4.45, 95% CI = 1.26–15.7, respectively). Conclusions: These findings support the hypothesis that certain polymorphisms in genes involved in DNA-repair and carriers of GSTM1 deletion have an increased risk of lung cancer in never-smokers exposed to residential radon.